“住” 在新加坡华语口语中的体貌功能 = The aspectual function of zhu in Singapore spoken Mandarin - 姚雯晴 Yow, Boon Cheng (2019)
有学者注意到“住”在普通话与马来西亚华语里除了动词和动词补语的语法功能之外，也表现出了持续体貌标记“着”的特征，如范丽芳（2008）、王晓红（2009）、韩爱珍（2011）。 “住”在新加坡华语口语里，于某些情况下也具有持续体貌标记的使用方式，但前人的研究并没有涉及到新加坡华语口语。 为了验证此观察，本研究从新加坡综艺节目着手，考证“住”在新加坡华语口语里的语法功能。本文也重点分析“住”能否替代“着”、以及替代后所持有的语法功能，从而考察“住”向体貌标记语法化的程度。 本文发现，除了用作补语，“住”在新加坡华语口语语料里有持续体貌标记以及补语兼持续体貌标记的使用方式。此外，“住”在替代“着”后，主要是跟动作动词搭配时会保留“着”持续体貌的特征，而出现在其它动词类型之后，主要还是用作补语。 本研究的结果证实了“住”在新加坡华语口语里已有虚化为持续体貌标记的迹象，但持续体貌标记并非“住”最主要的语法功能，也就是说“住”虽然出现语法化现象，但尚未高度语法化。 Besides being a verb and a verbal complement, zhu has been observed by several studies to carry the characteristics of the continuous aspectual marker zhe in Chinese Mandarin (Putonghua) and Malaysia Mandarin, e.g. Fan (2008), Wang (2009), Han (2011). The paper also noticed that zhu functions as a continuous aspectual marker under certain circumstances in Singapore Spoken Mandarin (SSM). However, previous studies have yet to focus on the aspectual function of zhu in SSM. In order to verify this observation, this study focuses on Singapore Variety Shows to examine the grammatical functions of zhu in SSM. Moreover, this study also examines the grammatical functions that zhu carries, after it takes over the position of zhe, so as to inspect the degree of grammaticalization of zhu. This study finds that zhu can serve as a continuous aspectual marker and a verbal complement-continuous aspectual marker in SSM. In addition, zhu generally retains the characteristics of the continuous aspectual marker zhe when it collocates with activity verbs, whereas it mainly serves as a verbal complement when it co-occurs with other verbs. The overall findings of this study show that zhu has commenced its gramamticalization into a continuous aspectual marker in SSM, but it is still at the initial stage of grammaticalization given that being an aspectual marker has not become the major grammatical function of zhu.